Installation Of Language In Communicating Early Children Age 5-6 Years - Setyaningsih, Aulia; Katoningsih, Sri (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2021)
Aim This study aims to examine the literature, articles and research documents that identify language maturation in communication in children aged 5-6 years. Method This study is a qualitative study with a literature review method based on reviews of national journals and international journals. The sampling technique used is reference in the form of primary articles of less than 20, 15 national journals with a period of 5 years and international journals with a period of 7 years that are quality, accredited and reputable. The results indicate that language maturation in communication can be done by sharing ways such as using flash cards, letterbox media, using songs during learning, using audio-visual media.